Validation of PET/MRI attenuation correction methodology in the study of brain tumours - De Luca, Francesca (BMC Med Imaging, 2020)
BACKGROUND: This study aims to compare proton density weighted magnetic resonance imaging (MRI) zero echo time (ZTE) and head atlas attenuation correction (AC) to the reference standard computed tomography (CT) based AC for (11)C-methionine positron emission tomography (PET)/MRI. METHODS: A retrospective cohort of 14 patients with suspected or confirmed brain tumour and (11)C-Methionine PET/MRI was included in the study. For each scan, three AC maps were generated: ZTE–AC, atlas-AC and reference standard CT-AC. Maximum and mean standardised uptake values (SUV) were measured in the hotspot, mirror region and frontal cortex. In postoperative patients (n = 8), SUV values were additionally obtained adjacent to the metal implant and mirror region. Standardised uptake ratios (SUR) hotspot/mirror, hotspot/cortex and metal/mirror were then calculated and analysed with Bland–Altman, Pearson correlation and intraclass correlation reliability in the overall group and subgroups. RESULTS: ZTE–AC demonstrated narrower SD and 95% CI (Bland–Altman) than atlas-AC in the hotspot analysis for all groups (ZTE overall ≤ 2.84, − 1.41 to 1.70; metal ≤ 1.67, − 3.00 to 2.20; non-metal ≤ 3.04, − 0.96 to 3.38; Atlas overall ≤ 4.56, − 1.05 to 3.83; metal ≤ 3.87, − 3.81 to 4.64; non-metal ≤ 4.90, − 1.68 to 5.86). The mean bias for both ZTE–AC and atlas-AC was ≤ 2.4% compared to CT-AC. In the metal region analysis, ZTE–AC demonstrated a narrower mean bias range—closer to zero—and narrower SD and 95% CI (ZTE 0.21–0.48, ≤ 2.50, − 1.70 to 2.57; Atlas 0.56–1.54, ≤ 4.01, − 1.81 to 4.89). The mean bias for both ZTE–AC and atlas-AC was within 1.6%. A perfect correlation (Pearson correlation) was found for both ZTE–AC and atlas-AC compared to CT-AC in the hotspot and metal analysis (ZTE ρ 1.00, p < 0.0001; atlas ρ 1.00, p < 0.0001). An almost perfect intraclass correlation coefficient for absolute agreement was found between Atlas-, ZTE and CT maps for maxSUR and meanSUR values in all the analyses (ICC > 0.99). CONCLUSIONS: Both ZTE and atlas-AC showed a good performance against CT-AC in patients with brain tumour.